Peranan Saksi Instrumenter Dalam Perkara Pidana Terkait Pembuatan Akta Notaris (Studi Kasus Perkara Nomor 25/Pid.Sus-Tpk/2020/Pn.Pdg) - yudhi Wirawan; Pujiono Pujiono (Notarius, 2022)
AbstractInstrumenteral witness is a witness in a notary deed and participates in the process of making a notary deed. In the presence of instrumenteral witnesses in reading the deed, they heard and knew what was contained and included in the deed, while it was the obligation for the instrumenteral witnesses to keep the contents of the deed secret. Therefore, this study aims to explain how the legal protection for instrumenteral witnesses in providing information regarding the confidentiality of the notary deed which is the evidence in a corruption case. The approach method used is normative juridical. The result of the research is that instrumenteral witnesses get legal protection. The intrumentary witness is only responsible for his knowledge, limited to the formality of the deed's inauguration, regarding the content contained in the deed is the sole responsibility of the notary, because the deed was made by the notary together with the parties who presented to the notary public. If there is a dispute over the deed involving an instrumenteral witness, it is sufficient for the witness to explain the formal requirements for the deed inauguration.Keywords : instrumenter witness; notarial deed; confidentiality of a deedAbstrakSaksi instrumenter yaitu merupakan saksi dalam sebuah akta notaris dan ikut serta dalam proses pembuatan akta notaris. Kehadiran saksi instrumenter dalam pembacaan akta mereka mendengar dan mengetahui apa yang tercantum dan dicantumkan dalam akta, sedangkan kewajiban bagi saksi intrumenter untuk merahasiakan isi akta. Oleh karena itu, Penelitian ini bertujuan untuk menjelaskan bagaimana perlindungan hukum bagi saksi instrumenter dalam memberikan keterangan terkait kerahasian terhadap akta notaris yang menjadi alat bukti dalam perkara korupsi. Metode pendekatan yang digunakan yuridis normatif. Hasil penelitian adalah Saksi instrumenter mendapatkan perlindungan hukum. Saksi intrumenter hanya bertanggung jawab terhadap pengetahuannya sebatas formalitas peresmian akta, mengenai isi yang terdapat di dalam akta itu adalah sepenuhnya tanggung jawab notaris, karena pembuatan akta itu dibuat oleh notaris bersama para pihak yang menghadap kepada notaris. apabila terjadi sengketa atas akta tersebut yang melibatkan saksi instrumenter maka saksi cukup menjelaskan persyaratan formalitas peresmian akta.Kata kunci : saksi instrumenter; akta notaris; kerahasiaan akta